A novel gene linked to Imipenem resistance in E. coli isolate lacking known Imipenem-resistance genes - Trang Thu Hoang; Huyen Thanh Thi Le; Sang Ngoc Nguyen; Ung Dinh Nguyen; Tuan Ngoc Tran; Cuong Hung Nguyen; Thang Quang Truong; Nam S. Vo; Duc Quang Le; Son Hoang Nguyen; Minh Duc Cao; Thi Minh Ngoc Dao; et al. (Scientific Reports)
Abstract Imipenem-resistant Escherichia coli strains represent a growing public health concern, posing a threat due to their resistance to last-resort antibiotics. Here, we present the discovery of the Imipenem-Linked Resistance Gene VIN (ILR-VIN) within E. coli isolates from Vietnam, revealing its absence in non-resistant E. coli and local bacterial species. ILR-VIN constitutes a previously unrecognized genetic element potentially linked to Imipenem resistance, with notable prevalence in Vietnamese E. coli strains.We conducted an in-depth examination of the genetic basis of Carbapenem resistance in E. coli strains causing urinary tract infections. In a set of 47 UTI strains, we identified five displaying Imipenem resistance, with four of them carrying known resistance genes. Interestingly, ECV219, despite exhibiting Imipenem resistance, lacked known resistance genes, suggesting an unreported resistance mechanism. Comparative genetic analysis revealed distinct genes in ECV219, indicating a novel Imipenem resistance gene. To assess its function, we conducted transformation experiments in E. coli Rosetta™(DE3)pLysS and performed bioinformatics analyses using BLASTp, InterProScan, and Pfam to characterize the gene’s structure and potential functions.Our study identifies ILR-VIN as a novel gene linked to Imipenem resistance in E. coli isolate lacking known Imipenem-resistance genes. Experimental evidence confirmed that ILR-VIN expression enhances bacterial survival under Imipenem stress, providing direct evidence of its role in resistance. This discovery highlights the importance of ongoing research into antibiotic resistance genes to develop effective treatment strategies against antibiotic-resistant bacterial infections.